Utilization Of Wood Dust Waste As Raw Material For Making Biocharcoal Briquettes In Bulakan Village, Sukoharjo District, Sukoharjo Regency - Aprianto*, Riski; Jamil, Muhammad Ihsan; Mahasin, Ghazy Nibraskara Adhi; Javier, Juan; Wirayudha, Ganda (Universitas Syiah Kuala, 2023)
The purpose of this activity is to provide counseling to the Bulakan Village community regarding the utilization of sawdust waste as raw material for making briquettes. This activity was carried out in Bulakan Village, Sukoharjo District, Sukoharjo Regency for 45 days. The method used in this activity is counseling and introduction to briquettes from sawdust waste. Counseling is carried out by conveying information about the dangers of sawdust waste and the benefits of briquettes as a more efficient fuel. The results of this activity show that the people of Bulakan Village have great potential in utilizing sawdust waste as raw material for making briquettes. In this activity, the Bulakan community learned to process sawdust waste into briquettes using simple tools and materials. The flame test results show that 200 grams of briquettes from sawdust waste can last for 45 minutes. The conclusion of this activity is that counseling on the utilization of sawdust waste as raw material for briquettes in Bulakan Village, Sukoharjo District, Sukoharjo Regency succeeded in increasing public awareness of the dangers of sawdust waste for humans and the environment and its potential as raw material for making efficient alternative fuels. The utilization of sawdust waste can improve the economy of the community in Bulakan Village, Sukoharjo District, Sukoharjo Regency.